Android Base Rapid Application Development for Learning Yanbu'a - Teguh Tamrin; Syamsul Ma’arif (Universitas Dian Nuswantoro and IndoCEISS, 2020)
Learning to read the Al Quran is a very important basic knowledge, especially for early childhood, because it serves as a foundation to increase love for the Qur'an and an increase in the sense of faith in Allah Subhanahu Wata'ala. The current learning model is still very conventional. The method of learning the Yanbu'a book in general still uses the rote method by reading the book and listening to it from the teacher. The impact of learning like that causes the child to be less enthusiastic about learning so it is easy to bo-san. Seeing these problems, it is necessary to make mobile-based applications that can make it easier and fun for children to learn the Yanbu'a book. In this study, we will discuss the development of the Yanbu'a learning method with the Rapid Application Development Method on Android which was built using the Construct 2 application. Students are increasingly facilitated in learning and interest in learning is increasing.